Gambaran kondisi kesehatan mental mahasiswa - Muh. Amri Arfandi; Rifka Anita Rahman; Regina Lenik Gah; Nur Asma; Ahnaf Zaky Mahendra; Adella Nadhif Rosandini (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2025)
vulnerable to mental health problems. Academic, social, and financial pressures can lead to depression, anxiety, and stress, negatively affecting their well-being and academic achievement. Purpose: To find out the mental condition of students. Method: A descriptive quantitative study used a cross-sectional design. A total of 275 students from 13 universities in Samarinda participated. Data were collected online using the DASS-21 questionnaire and analyzed univariately. Results: Most respondents were in the normal range for depression (67.3%) and anxiety (61.5%), but over half experienced stress (58.9%). Severe depression was found in 9.8%, severe anxiety in 13.8%, and severe stress in 16.7%. Female students tended to report higher levels of depression, anxiety, and stress compared to males. Students from private universities had higher anxiety and stress levels than those from public universities. Third- and fourth-year students reported higher stress levels than first-year students. Conclusion: Mental health problems among students are relatively high, especially stress, with differences observed based on gender, type of university, and year of study. Higher education institutions should provide psychological support services and implement promotive and preventive programs to improve student mental well-being. Keywords: Anxiety; College Students; Depression; Mental Disorders; Stress. Pendahuluan: Mahasiswa berada pada masa transisi remaja akhir menuju dewasa awal, yang membuat mereka rentan terhadap gangguan kesehatan mental. Tekanan akademik, sosial, dan ekonomi dapat memicu gangguan seperti depresi, kecemasan, dan stres, yang berdampak negatif pada kesejahteraan dan prestasi akademik. Tujuan: Untuk mengetahui gambaran kondisi mental mahasiswa. Metode: Deskriptif kuantitatif dengan desain cross-sectional. Sebanyak 275 mahasiswa dari 13 perguruan tinggi di Kota Samarinda menjadi responden. Data dikumpulkan secara daring menggunakan kuesioner DASS-21 dan dianalisis secara univariat. Hasil: Mayoritas responden berada dalam kategori normal untuk depresi (67.3%) dan kecemasan (61.5%), namun lebih dari separuh mengalami stres (58.9%). Depresi berat dialami oleh 9.8%, kecemasan berat 13.8%, dan stres berat 16.7%. Berdasarkan jenis kelamin, mahasiswa perempuan cenderung memiliki proporsi depresi, kecemasan, dan stres lebih tinggi dibandingkan laki-laki. Mahasiswa perguruan tinggi swasta menunjukkan tingkat kecemasan dan stres lebih tinggi dibandingkan mahasiswa negeri. Sementara itu, mahasiswa pada masa studi tahun ketiga dan keempat cenderung mengalami stres yang lebih tinggi dibandingkan tahun pertama. Simpulan: Gangguan kesehatan mental cukup tinggi pada mahasiswa, terutama stres, dengan perbedaan yang tampak berdasarkan jenis kelamin, jenis perguruan tinggi, dan masa studi. Institusi pendidikan tinggi perlu menyediakan layanan dukungan psikologis serta program promotif dan preventif untuk meningkatkan kesejahteraan mental mahasiswa. Kata Kunci: Depresi; Gangguan Mental; Mahasiswa; Kecemasan; Stres.